Kaedah Susur dan Lantun untuk Masalah Pengaturcaraan Linear Dua dan Tiga Dimensi - Mohd, Ismail; Jaafar, Azmi; Budin, Harun; Monsi, Mansor (Universiti Putra Malaysia Press, 1995)
In this article, a simple preliminary method called Bounce and Explore Method for solving linear programming problems is presented. To date, several methods for solving this problem have been published besides the widely known simplex method.